Analisis Penggunaan Campuran Material Batupasir dengan Batulempung untuk Material Perkerasan Jalan Tambang di PT Belengkong Mineral Resources Site Insani Baraperkasa Kabupaten Kutai Kartanegara, Kalimantan Timur - Muhammad Rayhan Fhadillah; Agus Winarno; Oktaviani, Revia; Tommy Trides; Windhu Nugroho (Retii, 2023)
In this planning, it is assumed that the CBR value of the subgrade used is the result of taking the CBR value of the field. From the results of the field CBR values obtained 7.158%. Based on Hasi plotting obtained a thick figure of 18.6 inches. That is, that the total thickness must be at least 18.6 inches above the subgrade. Road layer structure planning recommendation for 7.7 in thick subbase course using Clay R50 % sample with CBR value 29.31%, 7.3 in thick base course using Clay R40 % sample with CBR value 32.11%, and 3.1 in thick surface course using Clay R30 % sample with CBR value 36.87%.